EP1102 Post-therapeutic impact of gynecologic cancer on urinary symptoms, psychosexual health and quality of life. (1st November 2019) - Gayete Lafuente, S; Pérez, L; Miralpeix Rovira, E; Salvadó Salvadó, A; Farré, M; González Comadran, M; Castells, M; Sole-Sedeno, JM; Mancebo Moreno, G
Abstract : Introduction/Background: The survival rates improvement of oncogynecologic surgeries and adjuvant therapies has led to focus on their long-term effects. Lower tract urinary symptoms (LTUS), sexual dysfunction (SD) and impaired quality of life (QoL) have been described as common complications in survivors. Disruption of paracervical autonomic fibers during hysterectomy and radiation cystitis could be main LTUS causes; while psycho-affective deterioration may play great role on SD. Our aim was to assess changes on these aspects after oncogynecological radical treatment. Methodology: This prospective cohort study included oncogynecological patients (endometrial, cervical and ovarian) undergoing radical-intent treatment in our unit, March2017-June2018, classified according the received therapy. ERAS protocol (Enhanced Recovery after Surgery) was performed. Baseline features as age, surgical-obstetric history, comorbidities, emotional traits and relationship stability were considered. All patients were surveyed before and 6 months after treatment, using validated questionnaires: ICIQ-UI-SF (International-Consultation-Incontinence-Questionnaire) evaluating LTUS impact on QoL, CACV ('Cuestionario-de-Autoevaluación-de-Control-Vesical') for detrusor dysfunction, ISFS (Index-of-Feminine-Sexual-Function) measuring SD risk, and SF-12 providing QoL profile. Results: 67 patients were finally included, without finding differences in baseline characteristics among the 46 ones completing both surveys and analysed. Pre-treatment, 50.7% patients reported urinary incontinence (UI), 74.6% no sexual activity and all high QoL scores. In the follow-up, an UI worsening tendency with advanced age was found independently of treatment modality, not reaching statistical significance. Mental QoL score in SF-12 reduced ∼2.5 points if undergoing radiotherapy. SD did not differ from pre-treatment status. Conclusion: Urinary and sexual function, as global QoL, remained stable 6 months after oncogynecological treatment. Although LTUS is difficult to assess being common in gynecological patients baseline, special attention is recommended in older women to avoid UI worsening. Those receiving radiotherapy may benefit from mental QoL support. Further research with larger populations is needed to accurately assess the impact of radical oncogynecological treatments; probably leading to develop patient-targeted recovery programs. Disclosure: The authors declare no conflicts of interest. None received grant support for this study neither for other clinical or research activity, except for the inscription to the current congress for 3 authors that was funded by VIFOR Pharma (non related to the study we present).